Applied numerical analysis - Gerald, Curtis F.; Wheatley, Patrick O. ([S.l.] : Addison-Wesley, 1998)
The Sixth Edition of this classic text has retained the features that make it popular, while updating its treatment and inclusion of Computer Algebra Systems and Programming Languages. Interesting and timely applications motivate and enhance students' understanding of methods and analysis of results. This text incorporates a balance of theory with techniques and applications, including optional theory-based sections in each chapter. This edition has additional challenging problems and projects which show practical applications of the material. Also, sections which discuss the use of computer algebra systems such as MapleA (R), MathematicaA (R), and now MATLABA (R), facilitate the integration of technology in the course. Furthermore, the text incorporates programming material in both FORTRAN and C. The breadth of topics, such as partial differential equations, systems of nonlinear equations, and matrix algebra, provide comprehensive and flexible, coverage of all aspects of numerical analysis. This text is appropriate for students with mathematics, science, engineering, or computer science backgrounds.